Understanding The Health Hazards of Black Mold: An Overview of Environmental and Population-Based Risks - Ramadhansyah, Muhammad Fadli; Arumdani, Intan Sekar; Hanung Nurany; Ike Rachmawati; Laliyanto (Jurnal Serambi Engineering, 2025)
Black mold is a type of fungus that produces dangerous toxins known as mycotoxins, which can enter the body through inhalation, skin contact, or consumption of contaminated food. This fungus thrives in damp and dark environments and can cause various symptoms, including respiratory irritation such as cough, runny nose, sore throat, or difficulty breathing and skin problems such as rashes or itching. The research method employs a literature review approach using databases including Scopus, PubMed, Science Direct, SpringerLink, JSTOR, PlosONE, Google Scholar, and SINTA. This study examines the potential health risks of black mold, focusing on environmental exposure, vulnerable populations, health effects, and remediation strategies. The literature review reveals that black mold exposure frequently occurs in damp indoor spaces. Populations at greater risk include children, the elderly, individuals with weakened immune systems, and those with chronic respiratory diseases. Health effects range from mild symptoms, such as eye and nasal irritation, to severe conditions like lung infections and neurological disorders, especially with prolonged exposure. This study concludes that black mold poses significant health risks and emphasizes the importance of prevention and timely remediation to address indoor mold contamination.